The Influence Of Breast Care On Breast Milk Expentidurein Mothers Who Had NewDeliveryat Grandmed Hospital, Lubuk Pakam - Sari Desi Esta Ulina Sitepu; Selamat Tuahta Sipayung (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Mother's Milk (ASI) is an important intake for the growth and development and health of babies. One of the efforts to increase milk production is by means of breast care. Breast care is useful for expelling reflexes and milk production. The purpose of this research activity was to see the effect of doing breast care on milk output in mothers who had just given birth at Grandmed Lubuk Pakam Hospital. The type of research used in this study was a quasi experiment with a one group pretest-posttest design approach, using a purposive sampling technique. The application of breast care was carried out for 31 mothers who had just undergone the delivery process at Grandmed Lubuk Pakam Hospital. Data collection was carried out using observation sheets and providing interventions to perform breast care for mothers who had just undergone the birth process. Measurement of the amount of breast milk in mothers who had just given birth was carried out twice, namely before being given breast care and after doing breast care then the results were recorded on the observation sheet. The results of statistical tests using the paired test showed a value of p = 0.000, p <? (0.000 <0.05). The results obtained show that there is an increase in the amount of breastfeeding in mothers who have just undergone the delivery process before and after doing breast care. It is expected that mothers who experience problems in expressing milk, to do breast care so that the amount of milk increases. Nurses can minimize the use of analgesic drugs to reduce headaches and use warm compresses for non-pharmacological management.